Antimicrobial Peptide LL-37 Drives Rosacea-Like Skin Inflammation in an NLRP3-Dependent Manner - Yoon, S.-H.; Hwang, I.; Lee, E.; Cho, H.-J.; Ryu, J.H.; Kim, T.-G.; Yu, J.-W. (Elsevier B.V., 2021)
Rosacea is a chronic inflammatory skin disease characterized by immune response？dependent erythema and pustules. Although the precise etiology of rosacea remains elusive, its pathogenesis is reportedly associated with an increased level of antimicrobial peptide LL-37. However, molecular mechanisms underlying the progression of rosacea via LL-37 remain poorly understood. Here, we examined the potential role of LL-37 in rosacea-like skin inflammatory phenotypes at a molecular level. Our in vitro data demonstrated that LL-37 promotes NLRP3-mediated inflammasome activation in lipopolysaccharide-primed macrophages, indicated by the processing of caspase-1 and IL-1β. LL-37 was internalized into the cytoplasm of macrophages through P2X7 receptor？mediated endocytosis. Intracellular LL-37 triggered the assembly and activation of NLRP3-ASC inflammasome complex by facilitating lysosomal destabilization. Consistent with these in vitro results, intradermal LL-37 administration induced in vivo caspase-1 activation and ASC speck formation in the skin of Nlrp3-expressing, but not in Nlrp3-deficient, mice. Intradermal injection of LL-37 elicited profound recruitment of inflammatory Gr1+ cells and subsequent skin inflammation. However, LL-37？induced rosacea-like skin inflammation was significantly abrogated in Nlrp3-deficient mice. Furthermore, an NLRP3-specific inhibitor, MCC950, markedly reduced LL-37？triggered rosacea-like phenotypes. Taken together, our findings clearly indicate that NLRP3 inflammasome activation plays a crucial role in LL-37？induced skin inflammation and rosacea pathogenesis. ？ 2021 The Authors